Uporaba transkranialne stimulacije z direktnim električnim tokom pri otrocih in mladostnikih - Bizovičar, Nataša (Rehabilitacija (Ljubljana), 2017)
Transcranial direct current stimulation (tDCS) is a non-invasive method of brain stimulation that uses weak electrical currents (1-2 mA) and two electrodes (anode and cathode). The mechanism of action is via change in the cortical excitability of the brain. Up to now, very few studies have been performed showing that the use of tDCS in children is relatively safe and has positive effects in diseases such as cerebral palsy, autism and epilepsy. For dystonia there are mixed data regarding efficacy of tDCS. Further randomised controlled trials should be performed in the future to demonstrate the effectiveness and determine the exact parameters of the tDCS stimulation in children.
Keywords: autism; avtizem; brain plasticity; cerebral palsy; cerebralna paraliza; Child; Electric Stimulation; epilepsija; epilepsy; motnje gibanja; movement disorders; otrok; plastičnost možganov; rehabilitation; transcranial stimulation with direct electric current disorders; transkranialna stimulacija z direktnim električnim tokom